THE USE OF TIKTOK APPLICATION THE 3RD SEMESTER ENGLISH EDUCATION STUDENTS OF FBS UNM - Hidayah, Khusnul; Abduh, Amirullah; Samtidar, Samtidar (Universitas Negeri Makassar, 2023)
This study aimed to find out the role of TikTok application in helping the 3rd-semester students of FBS Universitas Negeri Makassar to learn English and the perceptions of the 3rd-semester students of FBS Universitas Negeri Makassar regarding the impact and effectiveness of using the TikTok application. This study used a descriptive qualitative method. The participants in this study were the third-semester English education students. The data was collected through surveys and interviews. Based on the findings, the participants gave positive perceptions and also the application has a positive role and impact on the development and deepening of the students' English. The data showed that the TikTok application can help students learn English by increasing the students’ vocabulary and improving their pronunciation. The students also feel the impact and effectiveness of the TikTok application on English language learning.